Pengujian Kandungan Informasi pada Peristiwa dimasukannya Saham dalam Daftar Indeks LQ45 - Kusumawati, Rita (Journal of Accounting and Investment, 2003)
The purpose of this study is to examine information content of stock inclusion in LQ45 index list. It is seen from whether there is abnormal return or not that can be obtained around the announcement date. It is also seen the increase and the decrease of stock liquidity and asymmetric information around the announcement date. The research samples were selected using purposive sampling method from all stocks registered in Jakarta Stock Exchange (JSE) during July 1997-July 2001 period. The sample stocks contained of 79 newly included stocks in LQ45 list during July 1997-July 2001 period. Â We find that market reacted positively toward the newly included stocks in LQ45 index list indicated by the existence of : 1) Significant positive abnormal return around announcement date; 2) Trade volume increasing(it meant that there was stock liquidity rate increasing); and 3) Bid ask spread decreasingÂ  after the announcement.